2018
DOI: 10.1029/2018ms001364
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible and Efficient Radiation Scheme for the ECMWF Model

Abstract: This paper describes a new radiation scheme ecRad for use both in the model of the European Centre for Medium-Range Weather Forecasts (ECMWF), and off-line for noncommercial research. Its modular structure allows the spectral resolution, the description of cloud and aerosol optical properties, and the solver, to be changed independently. The available solvers include the Monte Carlo Independent Column Approximation (McICA), Tripleclouds, and the Speedy Algorithm for Radiative Transfer through Cloud Sides (SPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(232 citation statements)
references
References 59 publications
(86 reference statements)
2
184
0
Order By: Relevance
“…In this section, a short evaluation of the simulated AOD against observations from the Aerosol Robotic Network (AERONET; Holben et al, 1998) is shown, as well as of PM 2.5 and PM 10 against observations from the AirNow and AirBase networks in the United States and Europe, respectively. The simulations evaluated here consist of 24 h cycling forecasts with meteorological initial conditions provided by an analysis and aerosol and chemical initial conditions provided by the previous forecast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, a short evaluation of the simulated AOD against observations from the Aerosol Robotic Network (AERONET; Holben et al, 1998) is shown, as well as of PM 2.5 and PM 10 against observations from the AirNow and AirBase networks in the United States and Europe, respectively. The simulations evaluated here consist of 24 h cycling forecasts with meteorological initial conditions provided by an analysis and aerosol and chemical initial conditions provided by the previous forecast.…”
Section: Discussionmentioning
confidence: 99%
“…Section 7 presents simulation results and budgets; Sect. 8 is dedicated to a preliminary evaluation of simulations against aerosol optical depth (AOD) observations from the AERONET network (Holben et al, 1998) and against European and North American PM observations.…”
mentioning
confidence: 99%
“…RTE and RRTMGP operate on multiple columns at a time to exploit this parallelism. The column dimension is innermost; despite good reasons for having the spectral dimension vary fastest (Hogan & Bozzo, 2018), this choice allows user control over vector length and can be easily adapted to different architectures. RTE and RRTMGP are agnostic to the ordering of the vertical axis.…”
Section: An Extensible Architecture For Flexibilitymentioning
confidence: 99%
“…The latest radiation code of ECMWF, ecRad (Hogan and Bozzo, 2016), was implemented in Meso-NH in 2017. This code is highly modular, which allows the user to conveniently choose between multiple options.…”
Section: Radiationmentioning
confidence: 99%